Peripheral Artery Disease Intervention: Drug-Coated Balloon vs Drug-Eluting Stent, A Long-Term Comparison. (27th August 2022) - Marzlin, Nathan; Jan, M. Fuad; Kostopoulos, Louie; Moreno, Ana Cristina Perez; Bajwa, Tanvir; Allaqaband, Suhail Q.
Abstract : Objectives . The aim of the study is to evaluate current trends and long-term durability of both drug-eluting stents (DES) and drug-coated balloons (DCB) in the treatment of peripheral artery disease (PAD). Background . PAD affects more than 200 million people worldwide. Endovascular treatment of critical PAD has advanced in recent years. DES and DCB have demonstrated superiority compared to balloon angioplasty or bare metal stenting. The current literature lacks any long-term, direct comparison. Methods . A retrospective analysis was completed on patients who had femoral-popliteal interventions from June 2014 to June 2018 with either DCB or DES. Patient medical data and lesion characteristics were retrieved using the Vascular Quality Initiative database. Outcomes were analyzed through December 2019. Primary endpoint of time to clinical event-driven target lesion reintervention (TLR) and secondary endpoint of all-cause mortality were examined. Results . Four hundred eighty-three patients with a total of 563 interventions met the inclusion criteria. Three hundred fifty-nine DCB and 204 DES were performed. Of the DCBs, 132 required bailout stenting at the time of procedure. The mean time for TLR in the DES group was 1, 277 days (SD 546), compared to 904 days (SD 330.1) for DCB. For patients requiring TLR, DES remained patent significantly longer (373 days longer on average) (p < 0.001). For all-cause mortality there was no significant difference at 50 months between DCB and DES (p = 0.06). Conclusions . In patients who required TLR, DES had a significantly longer length of time to reintervention vs DCB (average 373 days), although no difference in mortality was observed.